Ultrasound-Mediated Green Synthesis of Imidazo[1,2- a ]pyridines and Imidazo[2,1- b ]thiazoles through C(sp 3)-H Functionalization - Chauhan S.; Verma P.; Srivastava V. (My University, 2025)
An ultrasound-assisted expedient protocol has been developed for the synthesis of imidazo[1,2- a ]pyridines and imidazo[2,1- b ]thiazoles by the C-H functionalization of ketones using a KI/ tert -butyl hydroperoxide catalytic system. The reaction takes place in water, a green solvent, and does not require a metal catalyst; it also gives good yields of the products. The method offers numerous noteworthy characteristics, including mild reaction conditions, the absence of a base, broad functional-group compatibility, and excellent reaction yields. Moreover, it avoids the use of costly and air-sensitive chemicals, and can be conducted under ambient reaction conditions. © 2024. Thieme. All rights reserved.